ANALISIS PENGARUH MANAJEMEN RISIKO TERHADAP KINERJA KEUANGAN BANK - Brian Bona T. Situngkir; Kayla Namira Reiza Faris Balfas; Muhammad Ahza Arroyyan; Dwi Desi Yayi Tarina (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
This study aims to analyze the impact of risk management on banks' financial performance. The primary focus includes the management of credit risk, market risk, liquidity risk, and operational risk, each of which significantly affects banks' profitability, asset quality, and financial stability. Data and analysis reveal that effective risk management implementation can reduce potential losses, enhance operational efficiency, and maintain financial stability, especially in navigating economic challenges and market fluctuations. By employing strategies such as portfolio diversification, data-driven credit assessment systems, and optimal liquidity management, banks can improve Return on Assets (ROA), Return on Equity (ROE), and reduce Non-Performing Loan (NPL) ratios. This study concludes that integrated risk management is essential for ensuring sustainable financial performance in the banking sector.